Spain in the next 50 years: challenges ahead - Marcos, А. А. (Право и государство, 2013)
Spain is an old nation but a young democracy with a 35 years old Constitution. For this century Spain will face some challenges like ageing population, independentism and territorial integrity. In the other hand, Spain is a strong democracy inside the European Union and has a deep commitment with international community to foster freedom, democracy and human rights around the world, especially around the Mediterranean Sea.
Keywords: challenges; population; territorial integrity; political stability; European Union; democracy; human rights; international policy; community; Research Subject Categories::LAW/JURISPRUDENCE